The politics of monetary sector cooperation among the Economic Community of West African States members - Uche, Chibuike U. (Policy research working paper, 2001)
Meaningful regional integration among West African states is critical if the Economic Community of West African States (ECOWAS) is ever going to be be able to tackle civil wars, economic crises, and natural disasters in the region. France's support is essential for the development of a meaningful ECOWAS. Francophone West African countries face a choice betwwen closer ties with France, which has provided development aid, ensured currency convertibility, and guaranteed monetary stability in these francophone countries -- and closer ties with Nigeria [which has done none of the above for itself, much less for its neighbors, and has a different agenda from France]